NK cell destiny after haploSCT with PT-Cy - Peled, Amnon (Blood, 2018)
In this issue of Blood, Russo et al provide important insights on the effect of posttransplantation cyclophosphamide (PT-Cy) on natural killer (NK) cell recovery and function after haploidentical allogeneic stem cell transplantation (haploSCT).(1)